Saliva versus plasma cytokines as possible predictors of autism severity - Yu. Yu. Filippova; A. S. Alekseeva; E. V. Devyatova; K. A. Rusakova; A. L. Burmistrova (Медицинская иммунология, 2023)
The autism spectrum disorders (ASD) are now widely accepted as a pervasive, complex, heterogeneous neurodevelopmental disorders with multiple etiologies, subtypes, and developmental trajectories. There are no available and effective biomarkers for them. Immune dysfunction is seen as an important risk factor contributing to the neurodevelopmental deficit in ASD, and is signified, among other things, by an imbalance of cytokines in the brain and on the periphery. In recent years, saliva has been proposed as a biological material for diagnosing ASD, due to the accessibility and non-invasiveness of the method for its production. However, the question of whether salivary cytokine levels may be used as effective early biomarkers for autism requires further research, including saliva versus plasma/serum comparisons.Aim: a comparative analysis of the levels of cytokines: IL-6, IFNγ, TNFα, IL-1β, IL-4, IL-10, in saliva and blood plasma to identify possible markers of ASD and their severity in children.The study included 11 children with typical neurodevelopment (TDC) and 55 children with ASD, among whom 37 children had mild or moderate autism (according to CARS), and 18 children had severe autism. Samples of unstimulated mixed saliva and venous blood were simultaneously collected from all children. Salivary concentrations of cytokines: IL-6, IFNγ, TNFα, IL-1β, IL-4, IL-10 were determined by multiplex Luminex™ analysis. Plasma levels of cytokines were assessed by ELISA. Differences between groups were tested using the Kruskal-Wallis U-test with post-hoc Conover-Inman comparisons, between samples (saliva/ plasma) are using the Wilcoxon signed-rank test. The correlation between the concentrations of cytokines in plasma and saliva was determined using linear regression by the RMA method.In all examined groups, the levels of IL-6, IFNγ and IL-10 in saliva were significantly lower, and TNFα, IL-1β and IL-4 were higher than the corresponding levels of the same cytokines in plasma. Regardless of health/ disease status, no significant correlations were found between salivary and plasma cytokine levels in children. IL-1β levels were significantly lower and IL-10 levels were higher in the saliva of both groups of children with ASD compared with TDC. No significant differences in salivary cytokine concentrations were found between children with mild and severe ASD.Thus, salivary cytokines can be used as markers of ASD in children, but not the severity of the condition. The absence of correlations in the levels of some pro/anti-inflammatory cytokines between saliva and blood plasma may probably indicate a special immunological status of an ecological niche, the oral cavity.